2016
DOI: 10.1159/000448994
|View full text |Cite
|
Sign up to set email alerts
|

Association between Fetal Cerebral Ventriculomegaly and Platelet Alloimmunisation

Abstract: Introduction: Fetal and neonatal alloimmune thrombocytopenia (FNAIT) is a rare condition that may lead to intracerebral haemorrhage (ICH) in the fetus or neonate. Platelet alloimmunisation causing FNAIT has been described in association with fetal cerebral ventriculomegaly (VM), presumably due to subclinical ICH. The objective of this study was to assess the association between fetal VM and platelet alloimmunisation. Methods: This is a case series of pregnancies with fetal VM screened for platelet alloantibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Moreover, we were not able to analyze the association of fetal alloimmune thrombocytopenia with VM, as the investigation for platelet antibodies was not performed systematically. However, 11% screenpositive cases for platelet antibodies in a cohort of fetal VM have been reported recently, and no association with prenatal ultrasound findings, such as laterality, symmetry, or progression, was found [33].…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, we were not able to analyze the association of fetal alloimmune thrombocytopenia with VM, as the investigation for platelet antibodies was not performed systematically. However, 11% screenpositive cases for platelet antibodies in a cohort of fetal VM have been reported recently, and no association with prenatal ultrasound findings, such as laterality, symmetry, or progression, was found [33].…”
Section: Discussionmentioning
confidence: 92%
“…The frequency of positive serology for FNAIT in infants with isolated ICH is low . There is no confirmed association between FNAIT and isolated fetal brain anomalies such as fetal ventriculomegaly or fetal brain cysts .…”
Section: Methodsmentioning
confidence: 94%
“…Large cohort studies have reported on very few cases of FNAIT caused by GPIbIX alloantibodies . Apart from the difficulty in detecting them, anti‐GPIbIX alloantibodies are suspected to cause miscarriages, lowering the number of identified FNAIT cases that are dependent on anti‐GPIbIX alloantibodies .…”
Section: Discussionmentioning
confidence: 99%